Widening the Cracks in Consent: Reflections on the 2002 World Social Forum - Huet de Guerville, Diana; Clark, Charlie; Arsenault-May, Simone; Telfer, Lindsay (UnderCurrents: Journal of Critical Environmental Studies, 2002)
In the winter of 2002, a group of Master’s students from York University’s Faculty of Environmental Studies (FES) travelled to the second annual World Social Forum (WSF) in Porto Alegre, Brazil. This international meeting of social movements convened under the theme ’Another World is Possible’ and brought together an estimated 70,000 delegates from 131 countries. From January 31 to February 5, nearly 5,000 organizations lent their voices to the proceedings, and shared one overarching goal: to combat the negative effects of corporate globalization and offer an alternative to the worldview put forth by the financial and political elites at the World Economic Forum (WEF), which took place simultaneously in New York City.